A previously unknown cyclic alkanolamine and molecular ranking using the pair distribution function. Issue 6 (29th November 2021) - Gallo, Gianpiero; Terban, Maxwell W.; Moudrakovski, Igor; Huber, Tatjana; Etter, Martin; Ernst, Martin; Hinrichsen, Bernd; Dinnebier, Robert E.
Abstract : The crystal structure of a previously unknown small heterocyclic alkanolamine was determined by X‐ray powder diffraction. Total scattering analysis of small organic molecules is shown to be useful to help disambiguate spectroscopic and elemental analyses. Abstract : A new six‐membered cyclic alkanolamine with chemical formula C6 H15 N3 O3 was synthesized by the reaction of glycolaldehyde with gaseous ammonia. The molecular structure, characterized by a hexagonal ring of alternating carbon and nitrogen atoms with three hydroxymethyl groups attached to the carbon atoms, could not be unambiguously determined by elemental analysis and 1 H/ 13 C/ 15 N NMR. The molecular structure and conformation were further determined using a combination of vibrational spectroscopy (IR and Raman) and real‐space pair distribution function (PDF) analysis. The crystal structure was determined ab initio from laboratory X‐ray powder diffraction (XRPD) with orthorhombic space group Ama 2 (No. 40) and unit‐cell parameters a = 12.1054 (2) Å, b = 13.5537 (2) Å and c = 5.20741 (8) Å. Consistent structure models could be obtained by symmetry‐independent PDF and PDF‐Rietveld co‐refinements. Independent local structure refinements indicate that the most likely deviations from the average structure consist of small tilting and translational distortions of hydrogen‐bonded molecular stacks. Thermal analysis (TG/DTA) and temperature‐dependent XRPD measurements were also performed to determine the thermal behavior.